Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1440-1819.2009.02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of emotionally charged sounds in schizophrenia patients using exploratory eye movements: Comparison with healthy subjects

Abstract: Aims:  Emotion‐associated sounds have been suggested to exert important effects upon human personal relationships. The present study was aimed to characterize the effects of the sounds of crying or laughing on visual cognitive function in schizophrenia patients. Methods:  We recorded exploratory eye movements in 24 schizophrenia patients (mean age, 27.0 ± 6.1 years; 14 male, 10 female) and age‐matched controls. The total eye scanning length (TESL) and total number of gaze points in the left (left TNGP) and rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This finding extends previous research investigating exploratory eye movements in schizophrenia when confronted with audiovisual information, demonstrating that patients showed an increase in total number of gaze points when looking at a smiling face of a baby accompanied by laughter compared with processing the face in isolation ( Ishii et al , 2010 ). Therefore, presenting a congruent sound may increase visual attention and hence cortical processing of visual stimuli in patients.…”
Section: Discussionsupporting
confidence: 89%
“…This finding extends previous research investigating exploratory eye movements in schizophrenia when confronted with audiovisual information, demonstrating that patients showed an increase in total number of gaze points when looking at a smiling face of a baby accompanied by laughter compared with processing the face in isolation ( Ishii et al , 2010 ). Therefore, presenting a congruent sound may increase visual attention and hence cortical processing of visual stimuli in patients.…”
Section: Discussionsupporting
confidence: 89%
“…Differences in cultural background (Liu et al, 2015), social orientation (Ishii et al, 2010), and neuroticism (Brück et al, 2011) are known to alter neural responses to emotional auditory stimuli, and there are growing indications in the literature that cognitive biases present in highly anxious individuals promote differential sensitivity to the type and quality of vocal emotion cues they encounter (Kreifelts et al, 2014;Martin-Soelch et al, 2006;Peschard et al, 2014;Schirmer & Escoffier, 2010). To build on these insights, NOT THE FINAL VERSION we therefore monitored the relationship between core measures of (state or trait) anxiety and personality characteristics of our participants in the context of processing emotional vocalizations and emotional speech.…”
Section: Not the Final Versionmentioning
confidence: 99%
“…Ishi et al [17] reported that left TNGP EYE MOVEMENTS BETWEEN MOTHER AND BABY IN SCHIZOPHRENIA was smaller in schizophrenia patients under positive affection with voice and suggested that left eye scanning function could be a trait marker of schizophrenia, similar to previous reports [10]. In the present study, left TNGP under both versions (version 1: left mother, version 2: left baby) differed between patients and controls, especially depending on the location (left or right) of the mother.…”
Section: Conclusion and Psychophysiological Significancementioning
confidence: 99%